1984
DOI: 10.1212/wnl.34.11.1446
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of parkinsonism with L‐thereo‐3, 4‐dihydroxyphenylserine

Abstract: We have examined the kinetics of oral L-threo-3,4-dihydroxyphenylserine (DOPS) alone and combined with peripheral decarboxylase inhibitors in patients with Parkinson's disease and other degenerative diseases of the brain. Combined administration of L-threo-DOPS and carbidopa or benserazide produced higher plasma concentrations of L-threo-DOPS and suppressed the increase in plasma norepinephrine. This finding indicates some advantages of combined therapy with L-threo-DOPS and decarboxylase inhibitors. Measurabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In patients with neurogenic orthostatic hypotension in the setting of PD, treatment with Sinemet™, which contains carbidopa, would be expected to prevent pressor responses to L-DOPS, due to interference with the conversion of L-DOPS to NE (98). Neurogenic orthostatic hypotension in PD has gained attention only relatively recently (18).…”
Section: L-dops 195mentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with neurogenic orthostatic hypotension in the setting of PD, treatment with Sinemet™, which contains carbidopa, would be expected to prevent pressor responses to L-DOPS, due to interference with the conversion of L-DOPS to NE (98). Neurogenic orthostatic hypotension in PD has gained attention only relatively recently (18).…”
Section: L-dops 195mentioning
confidence: 99%
“…Neurogenic orthostatic hypotension in PD has gained attention only relatively recently (18). Inadequate consideration of effects of Sinemet™ treatment in this group might help explain variable results of clinical trials of L-DOPS to treat neurogenic orthostatic hypotension overall (6,65,98,108).…”
Section: L-dops 195mentioning
confidence: 99%
“…Clinical trials have shown the effectiveness of L-threo-3,4-dihydroxyphenylserine (L-DOPS), a synthetic norepinephrine precursor, on the freezing phenomenon (Narabayashi et al, 1981(Narabayashi et al, , 1987. However, it has been reported that free NE (Suzuki et al, 1984) and 3-methoxy-4-hydroxyphenylglycol (MHPG) (Yamamoto et al, 1986) concentrations in the CSF did not change after administration of L-threo-DOPS.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of DL-DOPS to increase cerebral NE concentration in humans, on the other hand, remains more controversial. Although DOPS has been detected in cerebrospinal fluid Narabayashi et al 1984), no significant changes have been observed in CSF levels of MHPG (Kondo and Narabayashi 1985;Ogawa et al 1985;Yamamoto et al 1985) or NE Sakoda et al 1985) following DOPS administration.…”
Section: Oisials~onmentioning
confidence: 99%
“…Langlais the freezing phenomenon in Parkinsonism (Narabayashi et al 1981(Narabayashi et al , 1984Ogawa et al 1985;Reches et al 1985;Yamamoto et al 1985). The results of chronic clinical trials, as well as detailed acute pharmacokinetic analysis and cardiovascular monitoring in humans ) and cats (Redmond et al 1975), have shown a lack of untoward side effects following DOPS administration.…”
mentioning
confidence: 99%